Conservation Agriculture and Household Food Security among Smallholders of Semiarid Areas of Kondoa, Tanzania - Khatibu, Salma (Tanzania Journal for Population studies and Development, 2025)
The rapid global population growth, particularly in Sub-Saharan Africa (SSA), is expected to significantly increase the demand for food by 2050 while agricultural productivity is inadequate. Conservation agriculture (CA) approaches have been recognised as possible remedy. This study was done semi-arid parts of Kondoa district, Tanzania, examined the effects of CA on households’ food security. Data were collected from 360 farmers through household surveys, employing both principal component analysis (PCA) and a multinomial endogenous treatment effects model to assess the impact of CA. The study found that CA practices significantly improve Household Dietary Diversity Scores per Adult Equivalent Unit (HDDS/AEU) and Household Food Insecurity Access Scale (HFIAS) scores. Factors positively influencing CA package adoption include farm size, household size, social group membership, and access to extension services. The study highlights the synergistic effects of combining multiple CA practices, which collectively have a greater impact on food security than individual practices. The findings underscore the importance of promoting CA practices as a strategy to enhance food security in semi-arid regions. Policymakers and agricultural extension services should focus on providing support and resources to farmers, including training, access to credit, and knowledge-sharing platforms.